(untitled) (The Batuk, 2022)
Personal financial planning is a tool that allows individuals to evaluate their current monetary situation, design strategies and implement them to achieve financial goals. This paper aims to analyse the determinants of financial planning of business graduates in Nepal. It examined the impact of financial attitude, financial awareness and financial knowledge on financial planning in the presence of gender, monthly income, family type, and marital status as control variables. A full-fledged questionnaire was used in the survey among 227 business graduates through email. Hierarchical multiple regression was used for the causal analysis. The findings revealed that financial attitude and financial awareness have significant impact on personal financial planning while financial knowledge does not. But surprisingly, none of the control variables were found significant in influencing personal financial planning. Hence, attitude and awareness towards the monetary aspects of life of business graduates are major determinants of their personal financial planning in Nepal.